PENGARUH PENGHENTIAN PAJANAN MONOSODIUM GLUTAMAT TERHADAP KADAR MALONDIALDEHID JARINGAN TESTIS TIKUS PUTIH (Rattus norvegicus) DEWASA - Puspasari, Ratih Hemiarista; Nawangsari, Nawangsari; Andriani, Andriani; Rahmayanti, Sari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2019)
Introduction: Monosodium glutamate (MSG) is a food additive that used as a flavor enhancers that can lead to oxidative stress in testis. Food and Drugs Administration (FDA) in 1995 has established the safety limit in the usage of MSG, no more than 120 mg/kgBW/day. Oxidative stress produce unstable and reactive lipid peroksidase that caused lipid degradation and generate malondialdehid (MDA). Objective: The purpose of this research was to observe MDA levels of testes after termination of MSG exposure. Method: This research was a true experimental research with simple random sampling. The control group (K) 1,2,3 were given aquades for 28 days. The first treatment group (P1) 1,2,3 were given MSG 4 g/kgBW/day for 28 days. The second treatment group (P2) 1,2,3 were given MSG 6 g/kgBW/day for 28 days and then stopped for 1 day, 28 days, and 56 days. Then, the rats were sacrificed and the testis was processed to be homogenate and then conducted to MDAâ€™s level measurements using Willâ€™s Methode. Data was analyzed using one way anova test, continued with post hoc test LSD. Result: Day 1 after MSG termination, analysis showed that there were significant difference between control group and the first group treatment 1 (p=0,010) and the second group treatment 1 (p=0,000). Day 29 after MSG termination, analysis showed that there was significant difference between control group and the second group treatment 2 (p=001), also between the first and the second group treatment 2 (p=0,017) . Day 57 after MSG termination, analysis showed there were no significant difference between the control group with both treatment group and between the treatment groups 1 to the treatment group 2 in. Conclusion: Termination of MSG exposure caused discontinuation of damage in rats testes. Keywords: Rats, Testis, Monosodium Glutamate, Oxidative Stress, MDA levelsSoft File NaspubÂ